2023
DOI: 10.1039/d2bm01595a
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent sialic acid materials for biomedical applications

Abstract: Sialic acid is a kind of monosaccharide expressed on the end of the non-reducing end of glycoproteins or glycolipids. It acts as the signal molecule combining with its natural receptor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 201 publications
(245 reference statements)
0
9
0
Order By: Relevance
“…Taken together, these studies suggest that multivalent inhibitors present obvious opportunities for therapeutic intervention. 131 While this prospect has yet to be realised in the clinic, several studies have demonstrated approaches to high affinity ligands for the influenza surface-presented NA and, to a lesser extent, HA.…”
Section: Potential Applications Of Sialic Acids In Protection Against...mentioning
confidence: 99%
“…Taken together, these studies suggest that multivalent inhibitors present obvious opportunities for therapeutic intervention. 131 While this prospect has yet to be realised in the clinic, several studies have demonstrated approaches to high affinity ligands for the influenza surface-presented NA and, to a lesser extent, HA.…”
Section: Potential Applications Of Sialic Acids In Protection Against...mentioning
confidence: 99%
“…Another study characterized the mechanisms of this therapeutic effect, namely the inhibition of intracellular autophagy during the life cycle of influenza viruses, which can expeditiously lead to a reduction in their amplification [ 51 ]. Based on these findings, tremendous efforts have been made to use multivalent Sia materials as antiviral agents [ 52 ]. Neu5Ac has been conjugated to various scaffolds such as polymersomes, liposomes, gold nanoparticles, and nanogels to amplify the effect of interfering with the viral infection process [ 53 ].…”
Section: Physiological Roles Of Neu5acmentioning
confidence: 99%
“…Multivalent interactions are widespread in nature and play important roles in biological processes, such as cell adhesion, growth regulation, , bacterial and viral infections, immune regulation and response, and DNA transcription . Multivalent carbohydrate–protein interactions are the key processes in a plethora of critical biological functions, including the adhesion of the influenza virus to cell membranes, the targeting cell recognition of carbohydrates with membrane receptors, and the immune response of carbohydrates with macrophages and dendritic cells. Novel therapeutic drugs based on multivalent carbohydrate–protein interactions have seen rapid development and clinical application in recent years, such as GalNAc-siRNA for hepatic targeting with the asialoglycoprotein receptor (ASGPR) and lysosome-targeting chimera (LYTAC) technology based on mannose-6-phosphate and GalNAc derivatives.…”
Section: Introductionmentioning
confidence: 99%